CRS Discussion of Bill C-86 - Centre for Refuge Studies, . (Refuge: Canada’s Journal on Refugees, 1992)
The Centre for Refugee Studies (CRS) held a discussion of the new amendments to the Immigration Act. A transcript of the discussion is presented.